The effect of integrated HIV/AIDS workplace programmes in improving management of HIV/AIDS by managers in the workplace : a case study of the education department, King William’s Town district - Gcadana, Buyelwa Carol (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil)--University of Stellenbosch, 2010.